Manufacture of oxy-acetylene thermally sprayed coating on refractory subtrates from unconventional feedstock material (2018)
A chromite mineral and two industrial residues produced in the petrochemical and thermoelectric industries, were selected, characterized, processed and deposited on refractory bricks. By means of X-ray fluorescence and X-ray diffraction the chemical composition and crystallographic phases of raw materials were analyzed, morphology and particle size was determinate using Scanning Electron Microscopy. The materials were deposit by oxyacetylene thermal spray on silica-alumina refractory bricks and high alumina low cement concrete, commercial references ER-40 and CBC-50 from ERECOS S.A.S.. The parameters used for the coating deposition were optimized based on preliminary test and simulations using the Jets&powders software. The chromite mineral coating displayed greater structure homogeneity than the other two coatings; the last ones presented partially melted particles and high porosity. However, based on the chemical composition, the response to adhesion test and the crystallographic phases present in the coatings, all of them are potential candidates to be used as protective barriers against corrosive effects on refractories.